A checklist and conservation status of the medicinal plants of Mount Arayat National Park, Pampanga, Philippines - MARLON DL SUBA; AXEL H ARRIOLA; GRECEBIO JONATHAN D ALEJANDRO (Biodiversitas Journal of Biological Diversity, 2019)
A checklist of medicinal plants in a natural area is fundamental not only it provides an updated reference but also it gives the current status of biodiversity.  In this study, available medicinal plants in Mt. Arayat National Park (MANP) was documented.  Existing and comprehensive references on Philippine medicinal plants were used to assess the medicinal values.  To determine their conservation status, the International Union of Conservation of Nature (IUCN) and list from the Department of Environment and Natural Resources (DENR) in the Philippines were accessed.  Results indicated a total of 60 species under 27 families were recorded in MANP.  Out of the 27 families, Leguminosae represented the highest number of medicinal plants and the genus Ficus has the most number of species.  Based on literature, most of the plants were used to treat infectious and parasitic diseases and diseases of the digestive system.  In terms of the conservation status, IUCN has assessed 6 vulnerable and 5 least concern species while DENR has listed 1 vulnerable species and the rest of the medicinal plants were marked as not evaluated.  This checklist provides data of various medicinal plants which aims to emphasize their uses and the need of conservation.